Trajectories of quality of life, health status and personal well-being up to two years after curative intent treatment for colorectal cancer: results from the UK ColoREctal Wellbeing (CREW) cohort study - Foster, Claire; Haviland, Joanne; Winter, Jane; Grimmett, Chloe; Chivers Seymour, Kim; Calman, Lynn; Batehup, Lynn; Corner, Jessica; Din, Amy; Fenlon, Deborah; May, Christine M.; Smith, Peter W.; et al. (Wiley, 2016)
Abstract of the presentation given at the British Psychosocial Oncology Society 2016 Annual Conference, 3–4 March 2016, Cambridge, UK.